Genetic Analysis of Antimicrobial Resistance in Salmonella Typhi: An Extensive Surveillance Study with National and Global Relevance - Ahmad, Maqsood; Rasool, Muhammad Hidayat; Aslam, Bilal; Khurshid, Mohsin (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: This study aimed to determine the prevalence and antimicrobial susceptibility patterns of multidrug-resistant (MDR) and extensively drug-resistant (XDR) Salmonella enterica serovar Typhi (S. Typhi) strains across multiple districts of Punjab, Pakistan. METHODOLOGY: A cross-sectional study was conducted across 15 districts in Punjab, Pakistan. A total of 7,993 blood cultures from febrile patients were obtained for the isolation and identification of S. Typhi, followed by antimicrobial susceptibility testing and screening for the resistance genes. RESULTS: A total of 2,832 (35.4%) blood cultures were positive for any bacterial growth. Of these positive cases, 1346 (47.5%) were identified as S. Typhi. High resistance rates were observed against several antibiotics: ciprofloxacin (91.8%), trimethoprim-sulfamethoxazole (86.1%), doxycycline (79.5%), and third-generation cephalosporins (46.5%). However, all isolates remained susceptible to carbapenems and azithromycin. The prevalence of MDR and XDR strains was 24.2% and 46.4%, respectively, with significant geographic variations in resistance patterns. Overall, the blaTEM gene was detected in 913 (67.8%) isolates. The resistance to cephalosporins was primarily mediated by the extended-spectrum beta-lactamase (ESBL) gene blaCTX-M-15, which was identified in 626 isolates (46.5%). The prevalence of blaCTX-M-15 varied considerably across different districts, with the highest rate observed in Kasur district (72.9%). CONCLUSION: This study reveals a significant public health concern, with a high prevalence of MDR and XDR S. Typhi strains, especially in certain districts. The findings support the use of azithromycin and carbapenems as empirical treatments in affected areas. Strengthened antimicrobial stewardship, targeted surveillance, and public awareness are crucial to address this rising threat.